LINGKUNGAN PEMBELAJARAN DAN HUBUNGANNYA DENGAN AKTIVITAS MUHADATSAH (STUDI IMPLEMENTASI PADA UPT MAâHAD DAN ASRAMA UIN AR-RANIRY BANDA ACEH) - Fajriah, Fajriah (Prodi PGMI FTK UIN Ar-Raniry Darussalam-Banda Aceh, 2016)
Language is a primary communication tool for human being to share ideas, thoughts, concepts and feeling. As communication tools ,of course, it is unseparable for mankind. It is very essential in life. Communication is one of the important things in human beingâs life. Moreover, speaking face to face is a vital communication way. If someone is able to speak well, it is surely that he or she is capable of delivering his goal and purpose well. In contrast, if someone is unable to speak well,it probably causes misunderstanding in communicating. In this case, how to construct a good language environment in teaching learning condition. The aim in writing this article is to increase the ability for practising Arabic for UPT students as well as in Maâhad and UIN Ar-Raniry hostel in Banda Aceh . It is not only in hostel setting but also in university area.